The Influence Of Entrepreneurial Capabilities On Marketing Performance Moderated By Digital Marketing : Study On MSMEs In Semarang - Cicik Harini; Retno Djohar Juliani; Leonardo Budi Hasiholan; Sugeng Bowo Handayani (Universitas 17 Agustus 1945 Semarang, 2024)
One way to contact clients, develop real-time connections with them, and ultimately win their pleasure is by using digital resources through digital marketing. With the use of digital marketing tools, this study aims to ascertain how entrepreneurial marketing affects marketing performance in Semarang, Indonesia. The research population The Area Sampling approach and the Stratified Random Sampling Technique were the two steps of the sampling approach used in this investigation. Path analysis using Smart-PLS software was the method of hypothesis testing adopted. The findings demonstrated that entrepreneurial marketing significantly and favorably affects marketing performance as well as digital marketing skills. Additionally, the performance of marketing is positively and significantly impacted by digital marketing skills. Nonetheless, there is less chance that digital marketing will act as a mediator in the connection between marketing performance and entrepreneurial marketing. Practically speaking, in order to sustain marketing performance, MSMEs must keep enhancing their skills and honing the application of entrepreneurial marketing strategies